The Ukrainian Campaign and the Development of New Operational Trends - A. A. Krivopalov (Проблемы постсоветского пространства, 2023)
Ongoing hostilities between Kiev and Moscow overturns the usual course of international relations in the post-Soviet space. It also forces political science to master related subject areas to figure out what is going on. A relatively stable frontline is one of this. This encourages discussing issues of military theory or recent military experiences. Highly likely new operational forms are emerging in the post-Soviet space, the comprehension of which is still a matter of an uncertain future.